“Simulation and Performance Analysis for Non-hermitian Symmetry DCO-OFDM Modulation in 100G-SWDM2 Datacenters Transmission System Based OM3/OM4 Fibers - SANYA, MAX FREJUS O.; CODJIA, Canisius M. B.; MAGNIDET, Fifamè Merci-Ange; BANDIRI, Sabi Y.M. (My University, 2024)
This paper investigates the performance of Non-Hermitian Symmetry (NHS) Direct-Current biased Optical OFDM (DCO-OFDM) in the context of 100G-SWDM (Short Wavelength Division Multiplexing) datacenters using OM3/OM4 fibers. OFDM is recognized for its robustness against optical fiber link distortion, while NHS exhibits low power consumption, leveraging its half computational complexity compared to Hermitian Symmetry in terms of optical OFDM modulator/demodulator. The study begins with a Bit Error Rate (BER) performance comparison between conventional DCO-OFDM and NRZ-OOK in a 100G-SWDM4 (25 Gb/s x 4) link. Based on the good distance transmission performed by DCO- OFDM, an implementation of NHS DCO-OFDM is realized in a 100G-SWDM2 (50 Gb/s x 2) architecture. The results, obtained through simulation with realistic component parameters, reveal that NHS DCO-OFDM, referred to as (new–DCO), achieves approximately four (04) to five (05) times the distance transmission allowed by NRZ-OOK in a 100G-SWDM4 link, depending on the use of OM3 or OM4 fibers. Additionally, the new–DCO demonstrates promising distance transmission capabilities of 370m for OM3 fiber and 650m for OM4 fiber in the simulated 100G-SWDM2 architecture. Consequently, the new–DCO emerges as a good candidate for datacenter transmission, surpassing current transmission distances demonstrated by SWDM alliance partners.
Keywords: Datacenter; SWDM; NHS DCO-OFDM; NRZ-OOK; OM3/OM4 fiber.